Investigation of the changes observed in scrotal circumference, and native and post-thaw semen characteristics in karayaka rams during the breeding and nonbreeding seasons - KULAKSIZ, R.; CEBI SEN, C. (Journal of the Hellenic Veterinary Medical Society, 2019)
The aim of the present study was to investigate and compare the impact of the breeding (BS) and non-breeding (NBS) seasons on scrotal circumference, and native and post-thaw semen characteristics in Karayaka rams. Six (6) Karayaka rams were used as semen donors, and ejaculates were collected with the aid of an artificial vagina during the BS (October-November) and NBS (April-May). Interestingly, sperm freezability was found to be higher in the NBS, when compared to the BS, and the sperm motility rate (36.00±2.74%, 55.0±3.24%) and percentage of abnormal sperm (44.00±1.90%, 57.00±2.09%) were found to significantly differ with season (P<0.05). In conclusion, the post-freezing sperm motility was better during the non-breeding season. Post-thaw sperm abnormality was higher during non-breading season. However, if ram semen is used fresh for AI, it can be collected and used during both during the breeding and non-breeding season.